2014
DOI: 10.1149/2.1091410jes
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Microanalysis of Thin Ionomer Layers by Scanning Transmission Electron Microscopy

Abstract: Optimized conditions for imaging and spectroscopic/elemental mapping of thin perfluorosulfonic acid (PFSA) ionomer layers in fuel cell electrodes by scanning transmission electron microscopy (STEM) have been investigated. The proper conditions were first identified using model systems of either Nafion ionomer-coated nanostructured thin film catalysts or thin films on nanoporous Si. These analysis conditions were then applied in a quantitative study of the ionomer through-layer loading for two differently-prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 22 publications
(28 reference statements)
0
78
0
Order By: Relevance
“…In order to observe Nafion ionomer more effectively, K. More et al utilized electron microscopes with higher resolution than SEM, such as TEM and STEM. 16,17 The idea of "staining" ionomers using Cs has also been explored, 17 and has become an important technique for observing ionomer materials by TEM.…”
Section: 9mentioning
confidence: 99%
“…In order to observe Nafion ionomer more effectively, K. More et al utilized electron microscopes with higher resolution than SEM, such as TEM and STEM. 16,17 The idea of "staining" ionomers using Cs has also been explored, 17 and has become an important technique for observing ionomer materials by TEM.…”
Section: 9mentioning
confidence: 99%
“…Besides the catalyst and support characterization, using atomic force microscopy (AFM) and TEM, Xie et al [15] showed that the ionomer content changes the sizes of C aggregates and the thickness of the ionomer film covering the C surface. In addition, recently advanced TEM techniques such as aberration-corrected scanning transmission electron microscopy (STEM) with energy-dispersive spectroscopy (EDS) [16], and electron tomography (ET) [17], coupled with cesium ion exchange, were able to provide information about the microstructure of the ionomer phase in the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Direct imaging of the three-dimensional ionomer network inside the electrode still remains a challenge. Advanced TEM techniques have been used to image the ionomer via either microtoming and two-dimensional imaging of a series of slices or via three-dimensional imaging (ET) for a few ionomer-coated carbon particles[16,17].…”
mentioning
confidence: 99%
“…The high sensitivity of PFSA ionomer to electron beam radiation damage via radiolysis represents the main limitation of the former strategy. Through the investigation of different model systems, Cullen et al [68] identified the optimal conditions (electron dose, temperature, acceleration voltage) to minimize fluorine losses during the acquisition of EELS or EDS spectra. High acceleration voltages and cryo (liquid N 2 ) conditions were employed to obtain high spatial resolution EELS maps of Nafion-Pt/C catalysts minimizing the beam damage.…”
Section: Mapping Ionomer In the Catalyst Layermentioning
confidence: 99%